Influence of carbon on electrochemical characteristics of the molten iron/slag interface. (10th January 2022) - Judge, W.D.; Paeng, J.; Azimi, G.
Highlights: Carbon greatly increases interfacial capacitance and excess charge density. Shift in potentials of zero charge show carbon causes specific adsorption. Esin and Markov coefficient shows carbon carries a net charge of +5.9 ± 2.6 in molten iron. Carbon is capillary active at the molten iron/slag interface. Abstract: Interfacial properties between molten iron and slag play important roles in many steelmaking processes but very little electrochemical features are known. In this work, the influence of carbon (1 to 4.5 wt%) on electrochemical interfacial properties between molten iron and slag was investigated at 1600 °C. Impedance spectroscopy was performed at various direct current biases to measure ohmic-corrected differential capacitance. Single and double integration of the latter was used to obtain excess charge density and electrocapillary curves. All alloys displayed potentials of zero charge cathodic to the rest potential, indicating the metal side of the electric double layer carries a positive charge at the rest potential. Anodic to the potential of zero charge, carbon causes a large capacitance peak, increases excess charge density, and steepens electrocapillary curves. This behaviour is characteristic of specific (chemical) adsorption at the metal/slag interface, as opposed to electrostatic (physical) adsorption. This was verified by observation of the Esin and Markov coefficient where carbon systematically shifted potentials of zero charge towards more negative values. Measurement of the Esin and Markov coefficient showed the charge number of carbon in molten iron to be +5.9 ± 2.6. Hence, carbon carries a net positive charge while dissolved in molten iron, brings excess charge density to the interface that increases capacitance, causes attraction between metal/slag, and reduces interfacial tension. While it is well known carbon is not surface active at the iron/gas interface, results show carbon is capillary active at the iron/slag interface. Graphical abstract: Image, graphical abstract